Demand-driven inventory optimization and replenishment : creating a more efficient supply chain - Davis, Robert A., 1947- (Hoboken, New Jersey : Wiley, 2013)
"Use demand driven optimized inventory and replenishment to overcome your supply chain weaknesses, and deliver business-maximizing resultsReviewing the fundamentals of inventory optimization so that you can attain a demand-driven supply, Demand-Driven Inventory Optimization and Replenishment provides a business look at why present inventory systems sub-optimize the supply chain and faulty replenishment processes lead to wasted time and effort. Straightforward and clearly written, this book allowsreaders to come away with a good understanding of why optimized inventory and replenishment helps overcome in-system weaknesses and deliver results. Discusses how multi-echelon inventory optimization and replenishment enables installed systems to go from a sequential, "islands of efficiency" approach to a systematic distribution system working as a complete network Provides case studies throughout Reveals how optimized inventory and replenishment delivers results across industry verticals With a historical view of the three major supply chain efforts of the last thirty years, this book discusses mathematical shortcuts set up in the transitional and supply chain management systems that make it very difficult for companies to attain supply chain excellence"--
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Business logistics; Inventory control; Delivery of goods -- Management; Customer services -- Management; Supply and demand; elektronické knihy; electronic books